PENGUNGKAPAN SUKARELA INTELLECTUAL CAPITAL DAN FAKTOR–FAKTOR YANG MEMPENGARUHI - Marfuah Marfuah; Sinta Purnawati (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
The purpose of this study was to examine the effect of firm size , profitability, leverage, ownership concentration, independent commissioners, and the firm age on the disclosure of intellectual capital. The study population was all the companies listed on the Indonesia Stock Exchange in 2011. By using purposive sampling method was selected as the study sample 138 companies. Based on multiple regression analysis, the results showed that the variables firm size, firm age, independent commissioners and profitability has a significant positive effect on the disclosure of intellectual capital , while the variable leverage and ownership concentration has no significant effect on the disclosure of intellectual capital. The results of this study indicate that the voluntary disclosure of intellectual capital in the company will increase with the increasing size of the company, the increasing age of the company, the magnitude of the proportion of independent commissioners and the increasing profitability of the company.